2013
DOI: 10.1002/pri.1574
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Levels of Immersion in Water on the Pulmonary Function and Respiratory Muscle Pressure in Healthy Individuals: Observational Study

Abstract: The results suggest that immersion at the level of the clavicles and xiphoid appendix alters lung function and respiratory muscle strength when compared with the values measured out of the water and immersed at the IC level in healthy individuals, demonstrating the influence of hydrostatic pressure on the respiratory system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Water immersion could assist the subjects to easily retain maximum expiratory phase, and it may be the reason why PImax was not impaired by water immersion in the present study. Regarding PEmax, our results support the findings of de Andrade et al 19 ) who reported that PEmax during water immersion did not differ regardless of the depth of the immersion. Primarily, submersion accompanied by decreases in VC and CC may be unfavorable conditions for measuring PEmax from the perspective of the length-tension relationship cited above.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Water immersion could assist the subjects to easily retain maximum expiratory phase, and it may be the reason why PImax was not impaired by water immersion in the present study. Regarding PEmax, our results support the findings of de Andrade et al 19 ) who reported that PEmax during water immersion did not differ regardless of the depth of the immersion. Primarily, submersion accompanied by decreases in VC and CC may be unfavorable conditions for measuring PEmax from the perspective of the length-tension relationship cited above.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, although it is considered that even in the RL trial, hydrostatic pressure against the lower part of thorax affected the expansion of the chest cavity, at least in part, there was no significant decrease in PImax following ILB in the RL trial, as well as in the UL trial. de Andrade et al showed that neither water immersion to the depth of iliac crest nor the xiphoid process level reduced VC compared to that measured on dry land 19 ) . Their findings suggest that immersion to the depth of the xiphoid process level or shallower does not yield enough hydrostatic pressure on the chest wall or venous return to the mediastinal space to impair the expansion of the chest cavity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We demonstrated that treadmill walking with an intensity corresponding to 60% of peak VO2 induced significant decreases in inspiratory and expiratory muscle strength only after walking in water. Respiratory functions, such as VC and FEV 1.0 , are known to be reduced by water immersion [20][21][22][23][24]. When submerged, hydrostatic pressure against the chest and abdominal wall causes inflexibility of the thorax and elevation of the diaphragm toward the cranial side, this reduces lung compliance and alveolar size at the end-expiratory phase of the respiratory cycle.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The hydrostatic pressure compresses the thoracic cavity, reducing its circumference, which promotes cranial displacement of the diaphragm. 2 In healthy individuals, the cardiovascular effects, which include increases in venous return, blood volume, and central venous pressure, result in increased cardiac output, greater left atrial diameter, and higher cardiac volume. 3 - 5 …”
Section: Introductionmentioning
confidence: 99%